Understanding Immigration : Issues and Challenges in an Era of Mass Population Movement - Hoskin, Marilyn B., 1945- (Book collections on Project MUSE., 2017)
"Based on the dual premise that nations need to learn from how immigration issues are handled in other modern democracies, and that adaptation to a new era of refugee and emigration movements is critical to a stable world, Marilyn Hoskin systematically compares the immigration policies of the United States, Britain, Germany, and France as prime examples of the challenges faced in the twenty-first century. Because immigration is a complex phenomenon, Understanding Immigration provides students with a multidisciplinary framework based on the thesis that a nation's geography, history, economy, and political system define its immigration policy. In the process, it is possible to weigh the influence of such factors as isolation, colonialism, labor imbalances, and tolerance of fringe parties and groups in determining how governments ultimately respond to both routine immigration requests and the more dramatic surges witnessed in both Europe and the United States since 2013."--Back cover.